2015
DOI: 10.1080/10408398.2013.794327
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Food Processing By-products as Dietary, Functional, and Novel Fiber: A Review

Abstract: Fast growing food processing industry in most countries across the world, generates huge quantity of by-products, including pomace, hull, husk, pods, peel, shells, seeds, stems, stalks, bran, washings, pulp refuse, press cakes, etc., which have less use and create considerable environmental pollution. With growing interest in health promoting functional foods, the demand of natural bioactives has increased and exploration for new sources is on the way. Many of the food processing industrial by-products are ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(109 citation statements)
references
References 84 publications
1
91
0
5
Order By: Relevance
“…On the other hand, drinkable yogurts with PFF showed a higher fiber content, which was in the range of 1.6-5.3%. These results are supported by the proximate composition of PFF, which evidenced its role as a rich source of soluble and insoluble fiber and its great potential to increase the nutritional value of drinkable yogurts and other food products [18].…”
Section: Proximate Compositionmentioning
confidence: 61%
“…On the other hand, drinkable yogurts with PFF showed a higher fiber content, which was in the range of 1.6-5.3%. These results are supported by the proximate composition of PFF, which evidenced its role as a rich source of soluble and insoluble fiber and its great potential to increase the nutritional value of drinkable yogurts and other food products [18].…”
Section: Proximate Compositionmentioning
confidence: 61%
“…There have been attempts at enriching bakery products with apple pomace, buckwheat pomace, grape pomace (Matejova, Fikselova, Curlej, & Czako, ), carrot pomace (Pandey, Kumar, & Mishra, ), and pitaya peel powder (Hsu, Chang, & Shiau, ). In other research, lettuce waste flour was used in wheat bread baking (Plazzotta, Sillani, & Manzocco, ); waste materials have high nutritional value and are a rich source of dietary fiber, mineral compounds, and antioxidant compounds (Sharma et al, ; Wang et al, ). Sayed‐Ahmad et al () showed that bread fortification with fennel cake and seed had beneficial effects on the phenolic concentration, the antioxidant activity, and the quality of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…high nutritional value and are a rich source of dietary fiber, mineral compounds, and antioxidant compounds (Sharma et al, 2016;Wang et al, 2018). Sayed-Ahmad et al (2017) showed that bread fortification with fennel cake and seed had beneficial effects on the phenolic concentration, the antioxidant activity, and the quality of the protein.…”
mentioning
confidence: 99%
“…These by-products are not put into use and hence create tremendous environmental pollution. There is growing interest in the formulation of health promoting and physiologically active foods and the demand of natural bio-actives available in these by-products are on the increase and it is possible to explore new sources for health promotion 16 . Many of these food industrial by-products are rich sources of dietary fibres and physiologically ingredients viz.…”
Section: Commercially Viable Approaches For By-products Utilisationmentioning
confidence: 99%